Unrealized Projects of Memorials to Heroes of the Great Patriotic War. To the Problem of the Soviet Memorial Ensembles Beginnings - Smirnova, Ksenia V. (Actual Problems of Theory and History of Art, 2013)
The article highlights some unrealized projects of memorial ensembles dedicated to the heroes of the Great Patriotic War, made up during the war and the early postwar years by Russian architects for Moscow and Stalingrad. The material originates from the funds of Schusev State museum of Architecture and State historical memorial “Stalingrad battle” in Volgograd. The projects represent the initial stage in the development of memorial complex typology. Some of them appear to be much more grandiose, than subsequent ones. The authors referred to antique and medieval architecture in search of inspiration, combining it with the Soviet symbols and images.
Keywords: Memorials to the heroes of the Great Patriotic War; art of the war period; Soviet art; memorial ensembles